Energy Audit for Energy Efficiency and Cost on Hospital Buildings - Putri, Mangesti Carissa; Devia, Yatnanta Padma; Susanti, Lilya (ASTONJADRO, 2024)
Hospitals are social facilities that operate publicly for 24 hours/day. The energy consumption of hospital buildings is among the highest, compared to commercial and residential buildings. Energy efficiency can be achieved after implementing a process called energy auditing and planning. The purpose of this study is to determine the EUI (Energy Use Intensity) of electricity for energy and cost savings, without reducing the productivity and comfort of the occupants. The method used in this research is the calculation of the EUI of the entire equipment, comparison of calculating the existing EUI with the Standard, simulation of existing conditions, redesign, modeling and simulation analysis of redesign results, calculation of EUI after redesign and calculation of energy costs before and after redesign. The results of this study obtained the EUI value in the air-conditioned room on the 1st floor of 15.14 kWh/m2/month included in the category Sufficient efficient from previously Wasteful, 2nd floor of 7.53 kWh/m2/month included in the category Fully Efficient and 3rd floor of 7.97 kWh/m2/month included in the category Fully Efficient. As for the non-AC room, the 1st floor of 2.27 kWh/m2/month is included in the Fully Efficient category, the 2nd floor of 2.50 kWh/m2/month is included in the Fully Efficient category from the previous Efficient, and the 3rd floor of 2.50 kWh/m2/month is included in the Fully Efficient category from the previous Efficient. Meanwhile, the calculation of energy costs after design recommendations was obtained at IDR 976.219.477,27 decreased by 21.56%.